PHYSICOCHEMICAL, PRELIMINARY PHYTOCHEMICAL AND ANTIBACTERIAL INVESTIGATION ON LEAVES OF CARDIOSPERMUM CANESCENS WALL. - G.PENCHALA PRATAP; G.SUDARSANAM; MOHD. KASHIF HUSAIN (International Journal of Pharma and Bio Sciences, 2014)
Effect of ethanol, methanol and petroleum ether extracts from the leaves of Cardiospermum canescens Wall. was studied against human pathogenic bacterial strains of Escherichia coli, Salmonella typhi and Klebsiella pneumonia and the antibiotic sensitivity of bacterial strains was also analyzed by using Bauer–Kirby method. Finally leaf powder was subjected to physicochemical and preliminary phytochemical evaluations to establish the quality and purity of the drug. In the Physicochemical studies, loss on drying, total ash value, acid insoluble ash, water insoluble ash, various extractive values etc., were carried out. Further, qualitative tests for various functional groups like triterpenoids, alkaloids, glycosides etc., were carried out. HPTLC profile was also established with ethyl acetate, and methanolic extracts. The results obtained from the study concluded that leaf powder of this plant is a great potential source as an antibacterial agent and preliminary phytochemical studies revealed the presence of triterpenoids, alkaloids, tannins, flavonoids and proteins.